2013
DOI: 10.1111/bju.12217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of serum prostate‐specific antigen isoform [‐2]proPSA (p2PSA) and its derivatives, %p2PSA and the prostate health index (PHI), in men with a family history of prostate cancer: results from a multicentre European study, the PROMEtheuS project

Abstract: Objectives• To test the sensitivity, specificity and accuracy of serum prostate-specific antigen isoform [-2]proPSA (p2PSA), %p2PSA and the prostate health index (PHI), in men with a family history of prostate cancer (PCa) undergoing prostate biopsy for suspected PCa.• To evaluate the potential reduction in unnecessary biopsies and the characteristics of potentially missed cases of PCa that would result from using serum p2PSA, %p2PSA and PHI. Patients and Methods• The analysis consisted of a nested case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 26 publications
4
78
0
1
Order By: Relevance
“…Within this range, more unnecessary biopsies can be spared compared with standard testing. These results have recently been supported by the DCA on a large ageindependent cohort with initial biopsies by Lazzeri et al [39] and Ferro et al [40].…”
mentioning
confidence: 58%
“…Within this range, more unnecessary biopsies can be spared compared with standard testing. These results have recently been supported by the DCA on a large ageindependent cohort with initial biopsies by Lazzeri et al [39] and Ferro et al [40].…”
mentioning
confidence: 58%
“…Previous studies have focused on the relationship between serum PSA and PV (Choi et According to these studies on serum PSA, there were strong relationship with PV, and they found that PSA would be able to predict the PV. Other studies on free PSA showed a loglinear relationship with PV and free PSA predicted PV more precisely than total PSA in BPH patients (Canto et al 2004, Lazzeri et al 2013). The ability of PSA to predict PV increased with prostate size.…”
Section: Discussionmentioning
confidence: 85%
“…The investigators from the PROMEtheus multicentre European trial have previously validated the use of the PHI in men with a positive family history of prostate cancer [4] Among the 965 participants in the PROMEtheus study, 14.7% were considered obese based on a body mass index ≥30 kg/m 2 . In this group, 45.8% were diagnosed with prostate cancer from a ≥12-core biopsy, and 67.7% had a Gleason score ≥7.…”
mentioning
confidence: 99%